Anthropometry and lifestyle in outpatients with Chronic Obstructive Pulmonary Disease: a descriptive study (Research, Society and Development, 2023)
Objective: evaluate anthropometric variables and lifestyle in outpatients with Chronic Obstructive Pulmonary Disease. Methods: a descriptive case series study, with a sample of 30 patients (age: ≥ 40 years) with a diagnosis of Chronic Obstructive Pulmonary Disease selected from the Pulmonology Clinic of a university hospital. Socio-demographic variables, behavioral aspects, weight, height, body mass index, weight change, arm circumference, calf circumference, waist circumference, hip circumference, waist-to-height ratio, waist-to-hip ratio and conicity index were analyzed. Results: 70% were older adults; 70% were male; 63.3% had < eight years of schooling; 76.7% were economically inactive; 66.7% had a household income ≤ the minimum salary; 83.3% were residents of the state of Pernambuco. The sample was made up predominantly of ex-smokers (83.3%) and smoked ≥ 20 years. A total of 66.7% had a sedentary lifestyle and 83.3% did not abuse alcohol. Excess weight was found in 50% of the sample and post-diagnosis weight loss was found in 50% of the sample. Abdominal fat was high in 56.7% based on waist circumference and 83.3% based on waist-to-height ratio; 53.3% had altered waist-to-hip ratio and arm circumference, ranging from malnutrition (40%) to ideal nutritional status (40%); 93% had a conicity index above the cutoff point. Based on the calf circumference, 84% of the older adults were classified as having ideal nutritional status. Conclusion: abnormal anthropometric measures and a sedentary lifestyle were found in the patients.